Pelatihan Pemanfaatan Galon Bekas Sebagai Produk Hiasan di Bank Sampah Semangka 8 Ds. Tambakasri Kec. Tajinan Kabupaten Malang - Saifuddin Karim; Agus Dwi Putra; Sugeng Pramudibyo; Yayi Febdia Pradani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Among various types of plastic waste, used gallon containers are among the most commonly found in household environments. The implementation method used in this activity is a training method, designed to enhance the skills of the mothers who are members of the Bank Sampah Semangka 8 Ds. Tambakasri, Kec. Tajinan, Kabupaten Malang, in processing used gallons into decorative products with market value. Through material introduction, demonstrations, independent practice, and discussions, participants not only learn technical skills but also gain valuable insights into the importance of recycling. The success of this training program can be measured by several outcomes, both in the form of products created and behavioral changes among participants. After attending the training, each participant is able to create at least three types of products from used gallons. This effort is expected to create a broader impact in raising collective awareness about the importance of sustainable waste management.